1995
DOI: 10.1084/jem.181.3.867
|View full text |Cite
|
Sign up to set email alerts
|

The T cell response of HLA-DR transgenic mice to human myelin basic protein and other antigens in the presence and absence of human CD4.

Abstract: SUITIH1 al'yAnalysis of HLA class II transgenic mice has progressed in recent years from analysis of single chain HLA class II transgenes with expression of mixed mouse/human heterodimers to double transgenic mice expressing normal human heterodimers. Previous studies have used either HLA transgenic mice in which there is a species-matched interaction with CD4 or mice which lack this interaction. Since both systems are reported to generate HLA-restricted responses, the matter of the requirement for species-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 43 publications
6
65
0
Order By: Relevance
“…Previously described HLA-DR1-transgenic mice (designated C57BL/6J 0-0 HLA-DR1) carrying full-length genomic constructs for HLA-DRA1*0101 and HLA-DRB1*0101 (26) were crossed for more than 6 generations to C57BL/6 A b -null mice (27) and genotyped by polymerase chain reaction for the presence of the HLA transgenes. This newly derived strain of DR1-transgenic mice lacked both human CD4 and endogenous mouse class II MHC molecules and was characterized by 1) a normal distribution of DR1ϩ lymphoid cell types in the spleen, 2) the expression of DR1 molecules on professional APCs, but not on CD4 or CD8 T cells, 3) a normal distribution of T cell receptor (TCR) V ␤ family expression among spleen cells, and 4) the susceptibility to CIA (Von Delwig A, et al: unpublished observations).…”
Section: Methodsmentioning
confidence: 99%
“…Previously described HLA-DR1-transgenic mice (designated C57BL/6J 0-0 HLA-DR1) carrying full-length genomic constructs for HLA-DRA1*0101 and HLA-DRB1*0101 (26) were crossed for more than 6 generations to C57BL/6 A b -null mice (27) and genotyped by polymerase chain reaction for the presence of the HLA transgenes. This newly derived strain of DR1-transgenic mice lacked both human CD4 and endogenous mouse class II MHC molecules and was characterized by 1) a normal distribution of DR1ϩ lymphoid cell types in the spleen, 2) the expression of DR1 molecules on professional APCs, but not on CD4 or CD8 T cells, 3) a normal distribution of T cell receptor (TCR) V ␤ family expression among spleen cells, and 4) the susceptibility to CIA (Von Delwig A, et al: unpublished observations).…”
Section: Methodsmentioning
confidence: 99%
“…Gated events (20,000) were counted for each sample. Animals C57BL/10.DQ8 transgenic mice carrying genomic constructs for DQA1*0301 and DQB*0302 and FVB/N.DR1 transgenic mice carrying genomic constructs for DRA1*0101 and DRB1*0101 have been previously described (8,9). For in vitro comparison of responsiveness to SMEZ, C57/BL10.DQ8 and FVB/N.DR1 transgenic mice both were used on a matched syngeneic (C57BL/10 ϫ FVB/N)F 1 background.…”
Section: Tcr-v␤ Repertoire Analysis In Vitromentioning
confidence: 99%
“…However, the outcome of the first trial (1) showed limited antimelanoma reactivity when compared with the application of tumor-infiltrating lymphocytes potentially because of the intermediate avidity of the TCRs used for transfer. TCRs with higher avidity for a tumor-associated self-Ag might be rarely isolated from autologous T cells, but rather be selected from T cells that recognize their target peptide in the context of a foreign MHC molecule or recognize allogeneic or xenogeneic peptides (3)(4)(5)(6). In fact, in the second clinical trial (2) two TCRs with specificity for MART1 and GP100 exhibiting higher avidity were transduced into PBMCs.…”
mentioning
confidence: 99%